2016
DOI: 10.3389/fpsyg.2016.00548
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Interference from Possessor Phrases in the Production of Subject-Verb Agreement

Abstract: We explore the language production process by eliciting subject-verb agreement errors. Participants were asked to create complete sentences from sentence beginnings such as The elf's/elves' house with the tiny window/windows and The statue in the elf's/elves' gardens. These are subject noun phrases containing a head noun and controller of agreement (statue) and two nonheads, a “local noun” (window(s)/garden(s)), and a possessor noun (elf's/elves'). Past research has shown that a plural nonhead noun (an “attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Whereas possessive case marking in languages like English and German precludes nouns from being grammatical subjects, Turkish requires genitive-marked subjects in non-finite embedded clauses. We hypothesized that if case information played a role in the selection of an appropriate controller for agreement, then attraction effects with possessors should occur in Turkish, in contrast with languages like English, where attraction from possessor modifiers has been reported to be non-existent or minimal (Nicol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas possessive case marking in languages like English and German precludes nouns from being grammatical subjects, Turkish requires genitive-marked subjects in non-finite embedded clauses. We hypothesized that if case information played a role in the selection of an appropriate controller for agreement, then attraction effects with possessors should occur in Turkish, in contrast with languages like English, where attraction from possessor modifiers has been reported to be non-existent or minimal (Nicol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both the attractor and subject head were third person nouns, always animate and human. The relationship between the possessor and the head noun was controlled for as it has been shown that it can influence the incidence of agreement errors (Nicol et al, 2016, Solomon & Pearlmutter, 2004. All subject noun phrases encoded a semantic relationship between the possessor and the head noun that could be appropriately paraphrased in English by using the possessive marker 's or the preposition of.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous production studies have shown that grammatical case modulates attraction in languages with case systems of different complexity (Russian: Lorimor et al, 2008;Nicol & Wilson, 1999;Dutch: Hartsuiker, Antón-Méndez, & van Zee, 2001;Slovak: Badecker & Kuminiak, 2007;English: Nicol & Antón-Méndez, 2009;Nicol, Barss, & Barker, 2016). One robust finding is that in languages where subjects always bear nominative case, a morphological nonnominative marker on the attractor reduces attraction, as compared to configurations where the subject head and the attractor share the same case form.…”
Section: Agreement Attraction In Turkishmentioning
confidence: 99%
“…
Speakers have been shown to find sentences with erroneous agreement acceptable under certain conditions. This so-called agreement attraction effect has also been found in genitive-possessive structures such as "the teacher's brother" in Turkish (Lago et al, 2019), which is in contrast to its absence in similar constructions in English (Nicol et al, 2016). It has been hypothesized that this discrepancy is a result of the association between genitive case marking and subjecthood in Turkish.We test an alternative explanation according to which Lago et al's findings are due to a potential confound in their experiment, as all subject head nouns were locally ambiguous between possessive and accusative case.
…”
mentioning
confidence: 94%